Mesoporous activated carbon yielded from pre‑leached cassava peels - Kayiwa, R.; Kasedde, H.; Lubwama, M.; Kirabira, J. B. (Bioresources and Bioprocessing, 2021)
The search for alternatives to fossil-based commercial activated carbon (AC) continues to reveal new eco-friendly potential precursors, among which is agricultural waste. The key research aspect in all these endeavors is empirical ascertainment of the core properties of the resultant AC to suit a particular purpose. These properties include: yield, surface area, pore volume, and the active surface groups. It is therefore pertinent to have process conditions controlled and tailored towards these properties for the required resultant AC. Pre-leaching cassava peels with NaOH followed by KOH activation and carbonization at holding temperatures (780 °C) above the melting point of K (760 °C) yielded mesoporous activated carbon with the highest surface area ever reported for cassava peel-based AC. The carbonization temperatures were between 480 and 780 °C in an activation–carbonization stepwise process using KOH as the activator at a KOH:peel ratio of 5:2 (mass basis). A 42% maximum yield of AC was realized along with a total pore volume of 0.756 cm3g− 1 and BET surface area of 1684 m2g− 1. The AC was dominantly microporous for carbonization temperatures below 780 °C, but a remarkable increase in mesopore volume (0.471 cm3g− 1) relative to the micropore volume (0.281 cm3g− 1) was observed at 780 °C. The Fourier transform infrared (FTIR) spectroscopy for the pre-treated cassava peels showed distortion in the C–H bonding depicting possible elaboration of more lignin from cellulose disruption by NaOH. A carboxylate stretch was also observed owing to the reaction of Na+ ions with the carboxyl group in the raw peels. FTIR showed possible absorption bands for the AC between 1425 and 1712 cm− 1 wave numbers. Besides the botanical qualities of the cassava peel genotype used, pre-leaching the peels and also increasing holding activation temperature above the boiling point of potassium enabled the modified process of producing highly porous AC from cassava peel. The scanning electron microscope (SEM) and transmission electron microscope (TEM) imaging showed well-developed hexagonal pores in the resultant AC and intercalated K profile in the carbon matrices, respectively.
Keywords: Activated carbon; Cassava peel; Pre-leaching; FTIR; Surface area and pore volume